SASTRA DAERAH “LEGENDA KAKEK SANG GERIGAP” SEBAGAI SARANA PEMBELAJARAN MORAL PADA SISWA - Hidajati, Enny (Jurnal Ilmiah Bina Edukasi, 2018)
Regional literature is a literature that lives and thrives in society and becomes a reflection of its people. Regional literature contains a philosophical life full of advice that contains a good moral message that can be a valuable learning for anyone. Unfortunately, there is a shift in value so that regional literature tends to be forgotten. The problem discussed in this research is how structural analysis of Levi-Strauss and what moral values ​​are contained in the story? Therefore, this study aims to analyze the folklore structurally to capture the learning of moral values ​​contained in LKSG. The method used is deskpitive. The approach used is the structural approach Levi-Strauss gives special attention to the myth. Discussion is divided into several episodes of the story to facilitate analysis. The results show that great powers are sometimes only myths that can be defeated with strong adhesions, confidence and use of common sense.